Familial aggregation of malignant mesothelioma in former workers and residents of Wittenoom, Western Australia - De Klerk, N.; Alfonso, Helman; Olsen, N.; Reid, Alison; Sleith, J.; Palmer, L.; Berry, G.; Musk, A. (2013)
Clustering of cases of malignant mesothelioma within families has often been observed, but disentangling genetic and exposure effects has not been done. Former workers and residents exposed to crocidolite at Wittenoom, Western Australia, where many families shared exposure to asbestos, have had high rates of mesothelioma. Our study aimed to estimate the additional risk of mesothelioma in relatives, after allowance for common exposure to crocidolite. More than 11,000 former asbestos workers and residents from Wittenoom have been followed up in cancer and death registries. Levels of exposure for all members of the Wittenoom cohorts have been estimated previously. Relationships between family members of all mesothelioma cases were established from questionnaires, birth and death certificates. Expected numbers of cases of mesothelioma were estimated by fitting a Weibull survival model to all data, based on time from first asbestos exposure, duration and intensity of exposure and age. For each family group, the earliest case was considered the index case. Predicted risk was estimated for each subject from the time of diagnosis of the index case. Familial risk ratios were estimated by dividing observed cases by the sum of risks of all same degree relatives of index cases. There were 369 family groups with at least one case of mesothelioma and a further 25 cases of mesothelioma among relatives in the same families, with 12.9 expected. The risk ratio for blood relatives was 1.9 (95% confidence interval [CI] = 1.3-2.9, p = 0.002). These findings suggest an important, but not large, genetic component in mesothelioma, similar to many other cancers. What's new? Familial clustering has long been observed in cases of malignant mesothelioma but it was difficult to separate increased exposure of families to asbestos at home from genetic factors. The Wittenoom cohorts in Australia are unique because they provide thorough estimates of asbestos exposure levels for families of workers, allowing a realistic differentiation between genetic and environmental risks. The authors find a 1.9-fold increase in risk for blood relatives, consistent with a small but potentially important genetic component to mesothelioma. Copyright © 2012 UICC.